“THE RELATIONSHIP BETWEEN GREEN ECONOMY AND MACROECONOMIC STABILITY IN UZBEKISTAN: AN EMPIRICAL STUDY” - Ochilov, Shokhrukh (Educational Research in Universal Sciences, 2023)
This is an econometric analysis of the relationship between the transition to a green economy and macroeconomic stability in Uzbekistan. The study uses a multiple regression model with GDP growth rate as the dependent variable and renewable energy development, energy efficiency, sustainable infrastructure investment, and foreign direct investment as independent variables. Data from the World Bank’s Development Indicators Database covering the period from 2000 to 2020 were used. The ARDL approach was employed to estimate the model, and the results show that all independent variables have a significant impact on the GDP growth rate, both in the short and long run. The study concludes that transitioning to a green economy can contribute to macroeconomic stability in Uzbekistan.